A QUALITY EVALUATION OF COMMON SPICES MARKETED IN PACKAGED AND UNPACKAGED FORMS - Dr. Ankita Srivastava; Pritika Joshi (The Bioscan, 2025)
Spices hold a pivotal position within the culinary traditions of India, esteemed for their unique flavors, alluring aromas, and health-promoting properties. However, the phenomenon of adulteration in spices has surfaced as a pressing concern, endangering food safety and public health. The objective of our study was to assess the quality of both packaged/branded and unpackaged/non-branded spices purchased in a metropolitan area. Furthermore, consumer perceptions and price differences were evaluated. A total of 70 spice samples (including 35 packaged and 35 unpackaged) were procured and subjected to rapid testing in accordance with FSSAI standards. The findings reveal that among the 35 unpackaged spices, all 35 were recognized as unhygienic and of inferior quality, whereas all 35 packaged spices were determined to be clean and safe. Findings of this study may aware people about using safe and hygienic spices, which is a major intention of food safety and quality management. We strongly recommend consumer awareness and monitoring of the enforcement of FSSAI standards that are crucial for ensuring the availability of pure and safe spices in the open market that is a major site for street food owners also.